FAKTOR - FAKTOR YANG MEMPENGARUHI TIMBULNYA NYERI PUNGGUNG BAWAH PADA KARYAWAN WORK FROM HOME DIMASA PANDEMI COVID 19 - Siti Sarah Bintang Sarah Bintang; Akhsan .; Rizka Mutiara; Miftahul Zannah; Delly Tunggal Febri Suryanto (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2021)
This study uses an observational design with a cross sectional approach 30 respondents who are currently still working at home during the COVID-19 pandemic have met the inclusion and exclusion criteria. The research instrument used was a questionnaire to assess work from home and a Nordic Body Map (processed in google form format) to measure back pain complaints of employees who work online/WFH. The data obtained were tested for normality with the Chi - Square test . The results showed there is no a relationship between the sexes with the onset of lower back pain in the employees work from home days of the pandemic COVID 19, the value of ?-value of 0.795 > ? (0.05) and t There is no relationship between years of service and the incidence of low back pain in employees working from home during the COVID-19 pandemic, the value of is 0.977 > (0.05). But there is a relationship between age and the incidence of lower back pain in the employees work from home days of the pandemic COVID 19, with a value of ?-value of 0.001 < ? (0.05), there is a relationship between length of employment with the onset of lower back pain in the employees work from home future pandemic COVID 19, with a value of p-value (0.000) < ? (0.05) and there is a relationship between working attitude with the onset of lower back pain in the employees work from home days of the pandemic COVID 19, with a value of ?-value of 0.002<(0.05).